The Impact of RES Curtailment Strategies for Congestion Avoidance on the Dynamic Frequency Performance of Low-Inertia Systems - Therapontos, Phivos; Aristidou, Petros (My University, 2023)
Network congestion due to excessive reverse power flow from distributed energy resources is one of the most pressing challenges for power system operators worldwide. There are several methods that can be used to alleviate congestion, however, most of them are either costly or currently not available to operators. RES curtailment strategies are frequently applied to reduce the reverse power flow and alleviate congestion issues. In this paper, we examine three such RES curtailment strategies and analyze their impact on RES penetration, frequency response, and available frequency containment reserves. The islanded electricity grid of Cyprus is used to showcase the results and suggestions are derived based on the operator priorities.
Keywords: congestion avoidance; frequency containment reserves; frequency stability; islanded systems; low-inertia systems; RES curtailment strategies